PENDEKATAN HISTORIS EMPIRIS DALAM STUDI ISLAM DAN IMPLIKASINYA - Khairudin, Khairudin; Zulkarnaen, Zulkarnaen; Mahrus, Mahrus; Ahadi, Abdi; Khojir, Khojir; Nursalim, Eko (STAI Syubbanul Wathon Magelang, 2025)
This research discusses the empirical historical approach in Islamic studies as one of the scientific methods used to understand Islam not only as a normative teaching but also as a historical phenomenon. This approach examines primary and secondary sources through verification of historical data and critical analysis of the socio-cultural context of a period. In modern Islamic studies, this approach is important because it is able to reveal the historical dynamics of the development of Islamic teachings, institutions and thoughts objectively. This research uses a qualitative method based on literature study, with results showing that the empirical historical approach has significant epistemological, methodological, and practical implications. The empirical historical approach in Islamic studies offers a more comprehensive view of Islam as an entity that develops in time and space. This approach does not only focus on theological or normative aspects, but also examines how Islamic teachings are practiced, interpreted and developed according to specific social, political and cultural contexts. By tracing the dynamics of history and using empirical evidence from the past, researchers can describe the transformation of Islamic thought and institutions more objectively and avoid ideological bias. In a methodological context, this approach requires precision in sorting and interpreting historical sources, both primary sources such as manuscripts, official documents, and secondary sources such as the results of previous studies. The data is analyzed critically by considering the socio-cultural background and power relations that influence an event or thought. The results show that the empirical historical approach not only enriches the treasures of Islamic scholarship, but also makes a real contribution in formulating Islamic responses to the challenges of modernity and contemporary social change.